A great mission of culture - Zaharenko, Igor A. (The New Research of Tuva, 2011)
Article presents the benchmarks of the biography of Aleksandr Adolfovich Palmbakh – a founder of Tuvan written language and literature.
Keywords: A. A. Palmbach; Tuvan language; Tuvan written language; literature; education; S. K. Toka; biography